Historical paintings from the 19th century and identity discourse: notes on iconography and the teaching of History in Paraná - Leopoldino, Maria Aparecida (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The article deals with the concept of historical time proposed in Brazilian textbooks regarding the pedagogical use of paintings about 19th-century Brazil which deal with the theme of indigenous culture. Cultural history guides the analysis that, methodologically, relates school history, memory and visual culture in order to approach a complex issue debated by Brazilian historiography about the uses of the past, memory and the way the history of Brazil was written and told, for a long time, from the perspective of the colonizer in the 19th and 20th centuries. In the unfolding of the relection, it is afirmed that the didactic challenges still remaining in the teaching of history come, faced with the necessity of teaching the problem, from the predominance of a conception of time which is characteristic of modernity. Results show the importance of putting the painters’ production in context so as to understand the interpretation that was made of the indigenous people at the time and the sense of difference the former built. It is concluded that the question remains current with regard to this teaching, mainly in colonized countries, and that putting the debate beyond what is considered civilized or uncivilized is essential for meaningful historical learning about cultural differences and, with them, temporal ones.